Neurofibromatosis type-1 with seizures and cerebrovascular malformation: a case study - Gopaal, Nishant; Sharma, Jagdish N.; Mathur, Priyanshu; Agarwal, Vijay; Jadoun, Laxman (International Journal of Contemporary Pediatrics, 2020)
Neurofibromatosis type 1 (NF1) is the most common autosomal dominant neurocutaneous among humans. Epilepsy is more prevalent in NF1 patients than in the general population. NF1 vasculopathy is also a significant but underrecognized complication of the disease, affecting both arterial and venous blood vessels. Herein, we report a 2 year old female child with seizures and multiple cafe-au-lait spots on the body. The patient was diagnosed with NF1 based on clinical findings and family history. MRI Brain revealed middle cerebral artery dysplasia. Here we discuss diagnostic and treatment challenges and briefly reviews the existing literature.